LEARNER AUTONOMY IN EFL/ESL CLASSROOMS IN BANGLADESH: TEACHERS’ PERCEPTIONS AND PRACTICES - Begum, Jahanara (International Journal of Language Education, 2018)
Abstract: In recent years, there has been a growing recognition of language teaching being more and more communication oriented. The traditional classroom teaching is facing a big challenge and is gradually being replaced by learner-centered approaches putting learner as individual into the core of learning process. This means learner autonomy gets to be enhanced to meet the need of the new teaching mode. While a great deal of researches have been done on the concept and development of learner autonomy , limited studies have investigated the ways and means of classroom practices of teachers in fostering learner autonomy in tertiary level EFL/ESL classrooms in Bangladesh. This paper examines what teachers think about learner autonomy as well as the strategies they use to develop learners autonomy in a university setting using a qualitative approach. The findings revealed that although university teachers are acquainted with what learner autonomy means, there are some challenges of developing learner autonomy in the classroom due to a number of lacking, such as teacher’s preparation, students’ reluctant attitude, suitability for different disciplined students and class timing.